PENGARUH SUKU BUNGA KREDIT, INFLASI, DAN PRODUCT DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP PERMINTAAN KREDIT INVESTASI DI PERBANKAN PROVINSI RIAU PERIODE 2002-2013 - Siti Mutia Setiani; Syapsan '; Anthoni Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the analysis of the Interest Rate, Inflation and The Gross Domestic Regional Product (GDRP) Variable to The Demand for Investment Loans in the Riau Banking. The data used in this study was a time series data from 2002 to 2013 were sourced from Bank Indonesia and Agency Investment and Promotion of Regional (Badan Penanaman Modal dan Promosi Daerah). This study used quantitative research methods, and analyzed by using multiple linear regression analysis by using SPSS 16 software program for Windows computers. In this study, the independent variable was Interest Rate (X1), Inflation (X2) and Gross Domestic Regional Product (GDRP) (X3) while the dependent variable was Demand for Investment Loans (Y).This study tested the hypothesis of regression coefficient (coefficient of determination, a significant test concurrent / F test, and the significant individual test / t test). The result showed the variable Interest Rate, Inflation and Gross Domestic Regional Product (GDRP) at once / simultaneously had a significant influence on the Demand for Investment Loans. The individual test / partial showed that Interest Rate variable acquired that contributes greater than the variable Inflation and Gross Domestic Regional Product (GDRP) to the Demand for Investment Loans.Keywords: Interest Rate, Inflation, Gross Domestic RegionalProduct (GDRP)and Demand for Investment Loans.